Involvement and targeted intervention of dysregulated Hedgehog signaling in osteosarcoma. Issue 4 (21st October 2013) - Lo, Winnie W.; Wunder, Jay S.; Dickson, Brendan C.; Campbell, Veronica; McGovern, Karen; Alman, Benjamin A.; Andrulis, Irene L.
Abstract : BACKGROUND: During development, the Hedgehog pathway plays important roles regulating the proliferation and differentiation of chondrocytes, providing a template for growing bone. In this study, the authors investigated the components of dysregulated Hedgehog signaling as potential therapeutic targets for osteosarcoma. METHODS: Small‐molecule agonists and antagonists that modulate the Hedgehog pathway at different levels were used to investigate the mechanisms of dysregulation and the efficacy of Hedgehog blockade in osteosarcoma cell lines. The inhibitory effect of a small‐molecule Smoothened (SMO) antagonist, IPI‐926 (saridegib), also was examined in patient‐derived xenograft models. RESULTS: An inverse correlation was identified in osteosarcoma cell lines between endogenous glioma‐associated oncogene 2 ( GLI2 ) levels and Hedgehog pathway induction levels. Cells with high levels of GLI2 were sensitive to GLI inhibition, but not SMO inhibition, suggesting that GLI2 overexpression may be a mechanism of ligand‐independent activation. In contrast, cells that expressed high levels of the Hedgehog ligand gene Indian hedgehog ( IHH ) and the target genes patched 1 ( PTCH1 ) and GLI1 were sensitive to modulation of both SMO and GLI, suggesting ligand‐dependent activation. In 2 xenograft models, active autocrine and paracrine, ligand‐dependent Hedgehog signaling was identified. IPI‐926 inhibited the Hedgehog signaling interactions between the tumor and the stroma and demonstrated antitumor efficacy in 1 of 2 ligand‐dependent models. CONCLUSIONS: The current results indicate that both ligand‐dependent and ligand‐independent Hedgehog dysregulation may be involved in osteosarcoma. It is the first report to demonstrate Hedgehog signaling crosstalk between the tumor and the stroma in osteosarcoma. The inhibitory effect of IPI‐926 warrants additional research and raises the possibility of using Hedgehog pathway inhibitors as targeted therapeutics to improve treatment for osteosarcoma. Cancer 2014;120:537–547 . © 2013 American Cancer Society . Abstract : Dysregulated Hedgehog signaling is investigated as a targeted intervention for osteosarcoma using small‐molecule modulators of the Hedgehog pathway in cell lines and IPI‐926 (saridegib), a specific Smoothened inhibitor, in patient‐derived xenograft models. Ligand‐dependent and ligand‐independent dysregulation and signaling crosstalk between the tumor and the stroma is identified and is supported by specific blockage of signaling exerted by the inhibitors.